A Cross-Sectional Study Investigating the Relationship Between Alexithymia and Suicide, Violence, and Dual Harm in Male Prisoners - Hemming, Laura; Shaw, Jennifer; Haddock, Gillian; Carter, Lesley-Anne; Pratt, Daniel (Frontiers in Psychiatry, 2021)
Background: Suicide and violence are common within male prisoners. One suggested risk factor for both behaviours is alexithymia. Alexithymia describes a deficit in identifying and describing feelings and is also related to externally oriented thinking. This study aimed to explore the relationship between alexithymia, suicide, violence and dual harm in male prisoners. Methods: Eighty male prisoners were recruited from three prisons. Participants were asked to complete a battery of questionnaires including measures of alexithymia (TAS-20), suicide ideation (ASIQ), suicide behaviour, violence ideation (SIV), violence behaviour, depression (BDI-II), hopelessness (BHS), impulsivity (DII) and anger (NAS-PI). Regression analyses and ANOVAS were conducted to assess the association between alexithymia (and its subcomponents) with six outcomes; suicide ideation, suicide behaviour, violence ideation, violence behaviour, dual harm ideation and dual harm behaviour. Results: Alexithymia was a univariate predictor of suicide ideation. though was not a significant predictor when considered in a multivariate model. when controlling for depression, Alexithymia was a significant multivariate predictor of suicide behaviour. Alexithymia was not a significant multivariate predictor of violence ideation or behaviour. There were no significant differences in alexithymia or subscales between those with suicide ideation / behaviour alone, violence ideation / behaviour alone and those with dual harm ideation / behaviour. Conclusion: In male prisoners, alexithymia appears an important univariate predictor of suicide and violence, though the current study suggests no significant contribution above other well-known correlates of suicide and violence.